PENGARUH PELATIHAN KERJA, MOTIVASI , DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SITUBONDO - Ainul Rizal Nadjid; Karnadi Karnadi; Lusiana Tulhusnah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The background of this research is that the Public Works and Spatial Planning Office of Situbondo Regency annually obtains the results of performance assessments on the implementation of work assignments, showing that not all have been able to achieve satisfactory work results. This research was conducted with the aim of knowing the partial, simultaneous, and dominant influence of Job Training, Motivation, and Leadership Style on Employee Performance at the Public Works and Spatial Planning Office of Situbondo Regency. The research method used is the method of observation, literature study, and documentation. The data analysis method used validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test, dominant test, and coefficient of determination. Based on the results of multiple linear regression, it shows that the variables are Job Training (X1), Motivation (X2) and Leadership Style (X3). Y = -3.465E-16 + 0.328X1 + 0.318X2 + 0, 253X3 + e The t-value for this Job Training variable is 2.990. While the value in the 5% distribution ttable is 2.003, then tcount 2.990> ttable 2.003 means Ho is rejected or Ha is accepted. The t-value for this motivation variable is 2.960. While the value in the 5% distribution ttable is 2.003, then tcount 2.960> ttable 2.003 means Ho is rejected or Ha is accepted. Meanwhile, the tcount value for this organizational commitment variable is 2,323. While the value in the 5% distribution ttable is 2.003 then tcount 2,323> ttable 2,003 means Ho is rejected or Ha is accepted Comparing the Fcount (16,218)> Ftable (= 2.76) based on statistical testing using the f test method, where the significant level obtained is 0.000 < 0.05. Showing the value of the coefficient of determination R square shows a value of 0.465, from these results it means that all independent variables (Job Training, Motivation, and Leadership Style) have a contribution of 46.5% to the dependent variable (Employee Performance) with a sufficient level of determination, and the rest of 53.5% influenced by other factors not included in the study.